Bile Acid Synthesis: From Nature to the Chemical Modification and Synthesis and Their Applications as Drugs and Nutrients - Šarenac, Tanja M.; Mikov, Momir (Frontiers in Pharmacology, 2018)
Bile acids (BAs) are amphiphilic molecules with 24 carbon atoms and consist of a hydrophobic and a rigid steroid nucleus, to which are attached a hydrophilic hydroxyl group and a flexible acidic aliphatic side chain. The steroidal core of BAs constitutes a saturated cyclopentanoperhydrophenanthrene skeleton, consisting of three six-membered (A, B, and C) and one five-membered ring (D). Primary BAs are produced in the hepatocytes, while secondary BAs are formed by modifying the primary BAs in the intestinal lumen, i.e., by the reactions of 7α-dehydroxylation and deconjugation of cholic acid (CA) and chenodeoxycholic acid (CDCA). The most important secondary BAs are deoxycholic acid (DCA) and lithocholic acid (LCA). The BAs realize their effects through nuclear farnesoid X receptors (FXRs) and membrane TGR5 receptors. It has been found that BAs are also associated with other receptors such as the vitamin D receptor (VDR), from which the most significant ligand is calcitriol, as well as with pregnane X receptor (PXR) and potentially with the constitutive androstane receptor (CAR), whose ligands are numerous, structurally different xenobiotics that show greater affinity to BAs. The BAs as therapeutic agents (drugs) have the potential to produce beneficial effects in cases of sexually transmitted diseases, primary biliary cirrhosis (PBC), primary sclerosing cholangitis, gallstones, digestive tract diseases, cystic fibrosis, and cancer. Ursodeoxycholic acid (UDCA) was the only drug approved by the US Food and Drug Administration (FDA) for the treatment of PBC. In this paper, the different pathways of bile acid biosynthesis are explained as well as chemical modifications and the synthesis of different keto derivatives of BAs. Also, the effects of BAs on digestion of nutrients, their role as drugs, and, in particular, the emphasis on the hypoglycemic properties of 7α, 12α-dihydroxy−12–keto−5β-cholanic acid in the treatment of diabetes mellitus are examined in detail.